Prevalence and socio-demographic correlates of HIV among Tuberculosis patients of DOTS centre in Delhi - Soyam, Vishal C; Das, Jyoti; TC, Rajeeva; Boro, Pallavi; Kohli, Charu (Asian Journal of Medical Sciences, 2015)
Background: Knowledge of HIV status of a TB patient is critical from both patient and public health point of view. Early HIV diagnosis among TB patients could serve as an entry point for HIV care and treatment. Surveillance of HIV among TB patients has been recognized to be important as the HIV epidemic continues to fuel TB epidemics. Hence, this study was conducted with an objective to assess the socio-demographic profile and the prevalence of HIV among TB patients. Methodology: Cross sectional study was carried out in eight DOTS cum DMCs of Delhi. Data was collected from January 2012 to December 2012. Registered TB patients (new and retreatment) were interviewed on a predesigned questionnaire at the end of five months of treatment. Results: In 2012, out of the total 552 TB patients interviewed, 524 (94.9%) had been tested for HIV by the end of fifth month of their TB treatment. In them, 13 patients (2.4%) were HIV positive. All of them had been initiated on ART and CPT during continuation phase of TB treatment. In present study no variable was found to be significantly associated with HIV status except number family member and patients on retreatment category. Conclusions: The prevalence of HIV infection in TB patients in current study was (2.4%) substantially lower than reported in studies from other states. If HIV testing done by all TB patients then routine reporting of HIV status for all TB patients would provide even better information on which to base future planning. Asian Journal of Medical Sciences Vol.7(1) 2015 53-58